2016
DOI: 10.4137/aswr.s35227
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Leaves as a Natural Adsorbent for the Removal of Cr(VI) from Aqueous Solutions

Abstract: Chromium(VI) has been found to be one of the toxic metals present in water obtained from industrial effluents. This study deals with the removal of Cr(VI) using used green tea leaves, which is a waste material. The sorption of Cr(VI) was carried out by using a batch method, and its concentration was determined using an ultraviolet visible spectrophotometer at 540 nm. Parameters such as pH, mass of adsorbate, concentration of adsorbent, time of contact, and temperature were optimized. It was observed that, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…However, it was determined that similar percentage removal results were achieved for the Pb and Cd ions at certain contact times and that there was no statistical difference between the results (p > 0.01). Similar findings have been reported in the removal of heavy metal ions by tea wastes 42 . In addition, some studies in the literature have reported similar results for heavy metals using different agricultural wastes 43,44 .…”
Section: Effect Of Btw Amount On the Adsorption Efficiencysupporting
confidence: 90%
“…However, it was determined that similar percentage removal results were achieved for the Pb and Cd ions at certain contact times and that there was no statistical difference between the results (p > 0.01). Similar findings have been reported in the removal of heavy metal ions by tea wastes 42 . In addition, some studies in the literature have reported similar results for heavy metals using different agricultural wastes 43,44 .…”
Section: Effect Of Btw Amount On the Adsorption Efficiencysupporting
confidence: 90%
“…optimum percentage removal of 99% ± 1%) at around 0.5 g of the adsorbent. Jeyaseelan and Gupta [8] observed similar results with the removal efficiency reaching a constant value at 0.8 g/50 ml adsorbent dosage of green tea leaves of Camellia sinensis plant species. The results obtained obviously follow such a trend due to more adsorption sites being available with the as amount of adsorbent increases.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 57%
“…The results obtained obviously follow such a trend due to more adsorption sites being available with the as amount of adsorbent increases. Since adsorption sites adsorbent particles increase, it would be more probable for CrO − ions to be adsorbed and thus adsorption efficiency should also increase as stated articulated by Bansal et al, [8]. In this particular case, the concentration of the Cr(VI) ions is constant and therefore increasing the adsorbent dosage increases the available adsorption surface area.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 89%
See 1 more Smart Citation
“…Even small amounts of Cr(VI) compounds can be harmful to human health [ 13 ]. Contact with Cr-containing materials often results in allergic reactions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%